USAHA PENINGKATAN PRESTASI BELAJAR MELALUI KETERAMPILAN MENJELASKAN SUB POKOK BAHASAN MODEL MATEMATIKA - Suparno Suparno (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2017)
The research objective is to describe (1) how far the skills of teachers in explaining the form of mathematical models. (2) student achievement through improving the skills of teachers while teaching in class XI Power Installation Engineering Department at SMK Negeri 2 Lamongan. This study uses three phases: pre-cycle, the first cycle and the second cycle. On average obtained pre-cycle - active student average is still 50% to 33.33% mastery learning outcomes, in cycle 1 active students gained an average of 64.30% and the percentage of learning outcomes is 59.26%. While on the second cycle of 27 gained an average of student activity increased to 80.56%, with a percentage of student learning outcomes that have been completed is 92.95%. Of the three stages is clear that there is an increase after application of learning.